Geographical differences in abundance and body size of calanoid copepods Pseudocalanus newmani and P. minutus in the Sanriku coast, Japan, during spring. - Yamada, Y. (Coastal Marine Science, 2022)
Pseudocanalus copepods dominate the Sanriku coastal area in the spring. In this study, the geographical changes in the abundance and body size of P. newmani and P. minutus in the nearshore and offshore waters of the northern and southern Iwate Prefecture were investigated. The abundance of P. newmani varied between 96 and 286,513 ind. m –2 and was significantly abundant in the nearshore stations. P. minutus appeared in the range of 0–1,610 ind. m–2 , and no significant differences were seen between the sampling stations. The mean prosome length (PL) of P. newmani and P. minutus at each collection ranged from 0.73 to 1.01 mm and from 1.02 to 1.38 mm, respectively, and were significantly different at each sampling time. For both species, significant negative correlations were recognized between PL and water temperature at the nearshore stations, however, not at the offshore stations. There were various types of water masses in the offshore area compared with the nearshore area, suggesting that the populations of Pseudocalanus copepods consist of a single local population in the nearshore area, whereas the offshore area may include populations with different origins. This suggestion is supported by the fact that the PL frequency distributions of Pseudocalanus copepods in the nearshore area were mostly monomodal, whereas those in the offshore area were generally multimodal.